Laundry Service Business Development Strategy for Aiko Laundry Cekok Babadan Ponorogo - Hamim Tohari; Hedi Pandowo; Koerniawan Dwi Wibawa; Chanif Kurnia Sari (Journal of Social Science and Humanities, 2025)
In the modern digital era, technology and social media play an important role in supporting businesses, including in the laundry business. This business is included in the category of micro, small and medium enterprises (MSMEs) engaged in the service sector. Aiko Laundry, located on Jalan Sunan Kudus number 74 Cekok Babadan Ponorogo, East Java Province, is an example of how MSMEs utilize technology in their operations. Aiko Laundry uses social media such as WhatsApp, Instagram, and Facebook for marketing and promotion strategies. Two payment methods are available for customers, namely conventional (pay on place) and digital (ATM, Mobile Banking, OVO, and Gopay). SWOT analysis was implemented by Aiko Laundry for the development of its business strategy. These results indicate that Aiko Laundry's business is feasible to be developed. Aiko Laundry's finances recorded a monthly turnover of Rp 6,570,800 and cash disbursements of Rp 2,890,000. This resulted in a net profit of around Rp 2,743,800. per month. Thus, in a year, Aiko Laundry can generate net income of around Rp 34,680,000. In the context of SWOT and social media, Aiko Laundry can take advantage of its strength in the use of social media for marketing and promotion (strength). Nevertheless, they need to maintain the quality of services to avoid weaknesses (weakness). The opportunity that can be taken by Aiko Laundry is an increase in social media and digital payment (Opportunity) users, while threats can come from competitors who also use social media in their marketing strategy (threat).